Directive Act Use in "Raya and the Last Dragon" Movie - Safitri, Ajeng Resva; Handayani, Nurma Dhona (EJI (English Journal of Indragiri): Studies in Education, Literature, and Linguistics, 2024)
This study identified the directive acts in the Raya in the last Dragon movie. In this study, the research design was a qualitative approach in which the researchers expressed the outcome in words and provided an explanation of the result. The researchers looked at a variety of directive speech acts. The purpose of this study is to pinpoint the directing speech act shown in the motion picture "RAYA AND THE LAST DRAGON" This study used a qualitative methodology, gathering data through reading the script, conducting library research, watching the film, and examining each character's speech and body language. A total of 15 directive speech acts were successfully identified by Kreidler (1998) using researchers who identified six utterances that embodied the commanding speech from the dialogue of characters, the other type is requesting type (3 data). The data referred to the conclusion of speech act. The data was taken from the movie conclude some point. First, Raya and the Last Dragon movie. Second, three utterances that reflected the requested speech were discovered by the researchers. Finally, the researchers discovered three utterances that expressed ordering speech from the movie's character utterances.